An adaptive clinical trial on patients with non variceal upper gastrointestinal bleed with the help of endoscopy - Singh, Prem; Singh, Gaurav; Kumar, Vinay; Chawla, Gaurav (International Journal of Advances in Medicine, 2020)
Background: Acute upper gastrointestinal hemorrhage (UGIH) is a common condition worldwide frequently leads to hospital admission also has a significant associated morbidity and mortality, especially in the elderly. A systematic diagnostic and definite therapeutic approach is essential to establish a diagnosis, relevant to specific investigations for appropriate treatment in tertiary medical care center. Methods: A comparative trial was done on n=109 cases with an objective to find out the different causes of UGI bleed in population, to assess the requirement of blood transfusion in patients with massive GI Bleed and to compare the treatment outcome of Proton pump inhibitors over Tranexamic acid and Octreotide in non-variceal UGI bleed. The cases were assigned to three different groups by lottery system. Proton pump inhibitors (Omeprazole), Somatostatin (Octreotide), Anti-fibrinolytic (Tranexamic acid), outcome was assessed after complete treatment and follow up. Results: Out of 150 cases, 109 were diagnosed with non-variceal GI bleed, 35 cases were treated with Omeprazole out of which 11.42% cases received blood transfusion, and 4 had history of re bleeding, Mean Duration of stay in hospital was 4.4±1.75, when compared to the other two group the duration of hospitalization was least as the P value was <0.0001. Conclusions: In this study it was demonstrated the use of PPI in case of Non-Variceal Bleeding significantly reduces the need of blood transfusion. Even it reduces the cases of re bleeding and duration of hospital stay.